Optimal systolic and diastolic blood pressure threshold that associated with lower risk of white matter hyperintensity progression - Liu, Sibo; Wang, Mengxing; Gu, De’an; Li, Yanzhao; Zhang, Xin; Li, Hang; Ji, Chenhua; Nie, Ximing; Liu, Jinjie (Frontiers in Aging Neuroscience, 2023)
Background The optimal control thresholds for systolic blood pressure (SBP) and diastolic blood pressure (DBP) in patients with white matter hyperintensity (WMH) are still unclear. Method A longitudinal retrospective study of patients with brain magnetic resonance imaging (MRI) scans with intervals of more than 3 years was conducted. Blood pressure records during hospitalization and from outpatient visits between baseline and the last MRI scan were collected. The outcome was the change in total WMH from baseline to the final visit. Results Among the 965 patients with MRI scans, 457 patients with detailed longitudinal blood pressure records were ultimately included and classified into the WMH absent group (n = 121), mild WMH group (n = 126), and moderate to severe WMH group (n = 210). Both baseline and longitudinal mean SBP, DBP, and SBP SD were significantly associated with WMH severity (p < 0.05). An average SBP of 130-140 mmHg [vs. <130 mmHg, aOR, 1.80, (95% CI, 1.05–3.07), p = 0.03] was associated with a higher risk of WMH progression. DBP ≥ 90 mmHg [vs. <80 mmHg, OR, 1.81, (95% CI, 0.88–3.74), p = 0.02, aOR, 1.54, (95% CI, 0.66–3.53), p = 0.32] was associated with a higher risk of WMH progression, but was not after adjusted for other covariates. Longitudinal BP variability was not significantly associated with WMH progression. Conclusion Both SBP and DBP had a stronger relationship with the severity of WMH. A target mean SBP of <130 mmHg and mean DBP of <80 mmHg was associated with a lower risk of WMH progression.